Technical and economic analysis of energy storage systems in smart grids - (:unkn) unknown (Institute of Electrical and Electronics Engineers Inc., 2017)
By managing the processes productively from power production to distribution to end user in smart grid systems, it is possible to store the energy when needed and then make it available for usage at a later time. This study analyses current and potential future electricity storage systems in smart grid technically and economically. © 2017 IEEE.
Keywords: Energy storage; Smart grids